Chlamydia and gonorrhoea infections in young Kenyan HIV-negative cisgender men who have sex with men and transgender women: a multicentre cohort study - Eduard J Sanders; Duncan Okall; Robert C Bailey; Fredrick Otieno; Susan M Graham; Joshua Kimani; Supriya D Mehta; Elise M van der Elst; Elizabeth Wahome; Alice Bentzer; Joseph Nzioka; Evans Gichuru (BMJ Open)
Objectives To assess the prevalence, incidence and factors associated with Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infection among HIV-negative men who have sex with men (MSM) and transgender women (TGW) in Kenya.Design Prospective cohort.Setting Kisumu, Nairobi and coastal Kenya.Participants 650 young adult participants (570 MSM and 80 TGW) recruited at three research clinics. Inclusion criteria were HIV-negative status, age 18–29 years, assigned male sex at birth, identification as cisgender male or transgender female and reported anal intercourse with a man in the past 3 months.Primary and secondary outcome measures Urine, rectal and oropharyngeal samples were tested for CT/NG infection at two different time points (∼6 months apart), using nucleic acid amplification. We compared CT/NG prevalence and incidence in MSM versus TGW and used Poisson regression to compare risk for each group after adjustment for other correlates of prevalent and incident CT/NG infection.Results Prevalence of CT/NG infection at any anatomic site was 15.8% and 27.5% in MSM and TGW, respectively (p=0.009). CT/NG incidence was 27.2 (95% CI 21.3 to 34.7) and 24.5 (95% CI 12.3 to 49.0) per 100 person years for MSM and TGW, respectively (p=0.784). In multivariable analysis, there was no difference in prevalence or incidence by gender identity. Baseline CT/NG infection was more prevalent among TGW (adjusted prevalence ratio 1.61, 95% CI 0.99 to 2.62). Incident CT/NG infection was increased among participants with baseline CT/NG infection (adjusted incidence rate ratio (aIRR) 3.14, 95% CI 1.94 to 5.07) and self-reported pre-exposure prophylaxis use (aIRR 1.75, 95% CI 1.04 to 2.93).Conclusion Despite higher prevalence of CT/NG infections among TGW at baseline, there were no differences in CT/NG prevalence and incidence between TGW and MSM, after adjustment for potential confounders. Improved condom use, effective partner notification and treatment, and new strategies such as doxycycline post-exposure prophylaxis are needed to reduce CT/NG infections in both MSM and TGW in settings where regular testing is not possible.